2016
DOI: 10.1159/000445663
|View full text |Cite
|
Sign up to set email alerts
|

CYP2J2-Derived EETs Attenuated Angiotensin II-Induced Adventitial Remodeling via Reduced Inflammatory Response

Abstract: Background: Cytochrome P450 (CYP) epoxygenases metabolize arachidonic acids (AA) to form epoxyeicosatrienoic acids (EETs), which exert beneficial roles in the treatment of cardiovascular diseases, but little is known about its role on adventitial remodeling. Methods: We used C57BL/6J mice in vivo and primary rat adventitial fibroblasts (AFs) in vitro treated with Angiotensin II to investigate the effects of CYP2J2 gene delivery and exogenous EETs administration on adventitial remodeling. Results: CYP/sEH syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 57 publications
0
21
0
Order By: Relevance
“…It is well recognized that interindividual variations in drug response, including a lack of efficacy and adverse drug reactions represent the major challenges for personalized medicine. Although a drug effect is complex and depends on many factors, some human gene polymorphisms already have been associated with substantial differences in the metabolism or effects of drugs [28], and some are now being used to predict toxic metabolite-related disease or a clinical response [29][30][31][32][33][34][35]_ENREF_1. _ENREF_1However, as the principal electron donor for the drug metabolizing CYPs, little is known about the effect of POR gene polymorphisms on the activities of CYPs with different genotypes.…”
Section: Discussionmentioning
confidence: 99%
“…It is well recognized that interindividual variations in drug response, including a lack of efficacy and adverse drug reactions represent the major challenges for personalized medicine. Although a drug effect is complex and depends on many factors, some human gene polymorphisms already have been associated with substantial differences in the metabolism or effects of drugs [28], and some are now being used to predict toxic metabolite-related disease or a clinical response [29][30][31][32][33][34][35]_ENREF_1. _ENREF_1However, as the principal electron donor for the drug metabolizing CYPs, little is known about the effect of POR gene polymorphisms on the activities of CYPs with different genotypes.…”
Section: Discussionmentioning
confidence: 99%
“…Inhibitors of sEH increased the EETs that mediated antiphlogistic actions, suggesting a new therapeutic approach for severe asthma [23]. In experimental studies, inhibitors of sEH have been shown to reduce lung injury caused by lipopolysaccharide [24,25], pulmonary fibrosis induced by bleomycin [15], asthma caused by OVA [12], and airway inflammation induced by cigarette smoke [26,27]. EETs can relax human airway smooth muscles and directly activate reconstituted KCa channels [28] and are potent modulators of the hyperreactivity triggered by TNF-α in human airway smooth muscle cells [29].…”
Section: Discussionmentioning
confidence: 99%
“…It has been previously shown that 14,15-EETs have important biological effects including anti-inflammation and anti-remodeling. Therefore, in our study we chose to study the anti-inflammation and anti-remodeling effects of 14,15-EETs [11,12]. All EETs, including 14,15-EETs, are metabolized to the less active dihydroxyeicosatrienoic acids by soluble epoxide hydrolase (sEH) [13].…”
Section: Introductionmentioning
confidence: 99%
“…Cardiac EET levels were analyzed using liquid chromatograph/mass spectrometer (LC/MS) as described previously (Zhou et al., ).…”
Section: Methodsmentioning
confidence: 99%
“…Transwell cell culture chambers (Corning, Cambridge, MA) with 8.0‐ μ m pore size polycarbonate membranes were used to evaluate cell migration ability in vitro as described before (Zhou et al., ).…”
Section: Methodsmentioning
confidence: 99%